Who's afraid of Virginia Woolf? Readers' responses to experimental techniques of speech, thought and consciousness presentation in Woolf's To the Lighthouse and Mrs Dalloway. (27th May 2020) - Grisot, Giulia; Conklin, Kathy; Sotirova, Violeta
Woolf's work has been the object of several studies concerned with her experimental use of techniques of speech, thought and consciousness presentation. These investigated the way in which different perspectives coexist and alternate in her writing, suggesting that the use of such techniques often results in ambiguous perspective shifts. However, there is hardly any empirical evidence as to whether readers experience difficulty while reading her narratives as a result of these narrative techniques. This article examines empirically readers' responses to extracts from Woolf's two major novels – To the Lighthouse and Mrs Dalloway – to provide evidence for whether Woolf's techniques for the presentation of characters' voices, thoughts and perspectives represent a challenge for readers. To achieve this, a mixed-methods approach that combines a stylistic analysis with a detailed questionnaire has been employed. Selected extracts that were hypothesised to be complex due to the presence of free indirect style and/or interior monologue were modified by substituting these with less ambiguous modes of consciousness presentation, such as direct speech or direct thought. Readers' responses to the modified and unmodified versions of the same extracts were compared: results show that the presence of free indirect style and/or interior monologue increases the number of perspectives identified by readers, suggesting that this technique increases the texts' difficulty, laying a more solid ground for future investigations.